Characterization of Indoor Air Bacterial Isolates from Rafidia Hospital, Nablus-Palestine - Ghaleb Adwan; Eman Abedraboo; Kamel Adwan; Suhaila Al-Sheboul (Archives of Current Research International, 2016)
Air can play a vital role as a reservoir for both pathogenic and non pathogenic living microorganisms. Microbial contamination of air hospitals is considered as a source of hospital-associated infections. This study aimed to assess microbial profile of air contamination in different wards of Rafidia Hospital, City of Nablus-Palestine, during the period September and October 2014, using both an active and a passive sampling methods. Results of this research showed that total viable count of Gram positive bacteria; coagulase-negative staphylococci (CoNS) and Micrococcus spp. were the most predominant among isolated bacteria from air samples in all surgical operation rooms (SOR), intensive care unit (ICU) and neonatal room (NR) by passive air sampling method. The percentage of CoNS and Micrococcus spp. in air of SORs, ICU and NR by passive air sampling has ranged from 61.8%-100% and the average was 5158 CFU/m2/h to 17753 CFU/m2/h. Staphylococcus aureus was the most common microorganisms isolated from the neonatal room by active air sampling method, the percentage was 100% and the average was 100 CFU/m3. Total bacterial level in these rooms had a range 116 CFU/m3 to 1085 CFU/m3. The percentage of CoNS and Micrococcus spp. in air from SORs and ICU by active air sampling was 58.8%-100% and the average was 100-1080 CFU/m3. The finding of this research showed that most frequent CFUs were obtained from Blood agar with a range 4085 CFU/m2/h to 8721 CFU/m2/h and Tryptic Soy Agar with a range 2043 CFU/ m2/h to 7935 CFU/ m2/h by passive air sampling method. In this study, ERIC PCR profile (number and size of bands) revealed that clinical bacterial strains S. aureus, E. coli and Klebsiella spp. and those isolated from air samples collected at the same time were not clonally related. This study is considered the first one to be conducted in Palestine in order to determine air bacterial isolates in SORs, ICU and NR. More studies are warranted on quality of air in these rooms. These data may be valuable to develop interventions to improve the microbial indoor air quality among hospital SORs, ICU and NR and also for preventing or decreasing the occurrence of the nosocomial infections.